Evaluation of personality disorders using the structured clinical interview for DSM-5 personality disorders, quality of life, and disease activity in patients with systemic lupus erythematosus - Yunus Durmaz,; İlker İlhanlı,; Pınar Durmaz, (Archives of Rheumatology, 2022)
Objectives: This study aims to determine the frequency of personality disorders in patients with systemic lupus erythematosus (SLE) and healthy volunteers and to compare SLE patients with and without personality disorders in terms of quality of life (QoL) and other clinical and laboratory findings. Patients and methods: Between January 2021 and March 2021, a total of 64 patients (17 males, 47 females; mean age: 42.9±10.8 years; range, 21 to 62 years) who were diagnosed with SLE and 68 age- and sex-matched healthy volunteers (20 males, 48 females; mean age: 40.9±10.6 years; range, 21 to 65 years) without any known disease were included. The Nottingham Health Profile (NHP) was filled in to evaluate the QoL for all participants. For the diagnosis of personality disorder, the Structured Clinical Interview For DSM-5 Personality Disorders (SCID-5PD) form was used. Clinical and laboratory findings of patients with SLE were noted and disease activity index (SLEDAI) was calculated. Clinical and laboratory variables that may affect personality disorder were evaluated. Results: The prevalence of personality disorder in SLE patients was significantly higher than the control group (39.1% vs. 11.8%, respectively; p<0.001). In terms of the subgroups of personality disorders detected in SLE, only the prevalence of obsessive-compulsive personality disorder was significantly higher than the control group (26.6% vs. 10.3%, respectively; p=0.015). The frequency of personality disorder increased, as the education level decreased, the duration of SLE disease increased, and with antiphospholipid autoantibodies positivity in patients with SLE (p<0.05). The mean NHP total score was 126.1±55.1 in SLE patients with personality disorder and 62.9±43.8 in patients without personality disorder, indicating that the QoL of SLE patients with personality disorder was worse than those without personality disorder (p<0.001). Conclusion: The frequency of personality disorder in SLE seems to be higher than in the control group. Quality of life is adversely affected in SLE patients with personality disorders. Therefore, clinicians should be alert for personality disorders that may accompany SLE and fight with personality disorder with early diagnosis and optimal treatment.